PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTION - Alimuddin Sa'ban Miru; Muhammad Nurfauzi; Sanatang Sanatang (Universitas Khairun, 2022)
This study aims to determine the increase in student learning outcomes in the class XI TKJ network service technology subject at UPTD SMK Negeri 1 Sinjai through the application of the cooperative learning model of the explicit instruction type and to determine student responses in applying the explicit instruction learning model. This research is a classroom action research which consists of four stages, namely action planning, action implementation, evaluation and reflection. This research was conducted in two cycles. Data analysis techniques were carried out after data collection. The data analysis used is descriptive statistical data analysis. The results showed that student learning outcomes in the class XI TKJ network service technology subject at UPTD SMK Negeri 1 Sinjai through the application of the explicit instruction type cooperative learning model increased. Therefore, it is suggested to teachers and schools to apply explicit instruction learning models to the learning process in schools.